Prevalence of mental health disorders in children and adolescents in the Republic of Ireland: a systematic review. (26th March 2023) - Lynch, S.; McDonnell, T.; Leahy, D.; Gavin, B.; McNicholas, F.
Abstract: Referrals to Child and Adolescent Mental Health Services (CAMHS) have increased in recent years. Services are already under-resourced and the adverse psychological impact of Covid-19 is likely to increase demand. Accordingly, an understanding of prevalence of mental health (MH) disorders among youth is imperative to help inform and plan services. Aim: To establish prevalence of MH disorders among youth (under 18) in Ireland. Method: A systematic review using pre-defined search terms in PubMed, PsycInfo, Embase and CINAHL was conducted. Empirical studies conducted in Ireland, in youth and focusing on MH disorders were included. Results: From a total of 830 papers identified, 38 papers met inclusion criteria. Significant variation in rates of MH disorders was evident based on study methodology. Screening questionnaires for general psychopathology reported rates of 4.8–17.8% scoring above clinical cut-offs, with higher rates for ADHD (7.3%). Studies examining depression ranged from 4% to 20.8%, while rates for 'current' MH disorder, determined by semi-structured interview, were 15.5%, while 'lifetime' rates varied from 19.9% to 31.2%. Fewer than half (44%) of those identified as 'in need' of specialist MH services were accessing CAMHS Conclusion: Data on MH disorders among Irish youth is limited, and studies showed significant variance in rates, making service planning difficult. There is an urgent need for serial epidemiological surveys, with clear operational criteria for clinically impairing MH difficulties. Such studies are essential to understand potential demand and service planning. This is most urgent given the expected increased demand post Covid-19.